A core domain set for hidradenitis suppurativa trial outcomes: an international Delphi process5. (5th July 2018) - Thorlacius, L.; Ingram, J.R.; Villumsen, B.; Esmann, S.; Kirby, J.S.; Gottlieb, A.B.; Merola, J.F.; Dellavalle, R.; Nielsen, S.M.; Christensen, R.; Garg, A.; Jemec, G.B.E.; et al.
Summary: Background: There is no consensus on core outcome domains for hidradenitis suppurativa (HS). Heterogeneous outcome measure instruments in clinical trials likely leads to outcome‐reporting bias and limits the ability to synthesize evidence. Objectives: To achieve global multistakeholder consensus on a core outcome set (COS) of domains regarding what to measure in clinical trials for HS. Methods: Six stakeholder groups participated in a Delphi process that included five anonymous e‐Delphi rounds and four face‐to‐face consensus meetings to reach consensus on the final COS. The aim was for a 1 : 1 ratio of patients to healthcare professionals (HCPs). Results: A total of 41 patients and 52 HCPs from 19 countries in four continents participated in the consensus process, which yielded a final COS that included five domains: pain, physical signs, HS‐specific quality of life, global assessment and progression of course. A sixth domain, symptoms, was highly supported by patients and not by HCPs but is recommended for the core domain set. Conclusions: Routine adoption of the COS in future HS trials should ensure that core outcomes of importance to both patients and HCPs are collected. Abstract : What's already known about this topic? Outcome measure instruments used for hidradenitis suppurativa (HS) are markedly heterogeneous with 30 instruments recently found in 12 randomized trials. Lack of consensus regarding outcome measure instruments limits evidence synthesis and increases the risk of outcome reporting bias. A core domain set is an agreed minimum set of what to measure that should be reported in all clinical trials of a specific condition. What does this study add? Our study provides global multistakeholder consensus on core outcome domains for HS. The final core domain set includes five domains: pain, physical signs, HS‐specific quality of life, global assessment and progression of course. A sixth domain, symptoms, was highly supported by patients and not by healthcare professionals; it is recommended by the steering committee as an additional core domain, in the context of being a patient‐reported domain. What are the clinical implications of this work? The routine adoption of this core outcome set in future HS trials should ensure that outcome domains of importance to both patients and HCPs are included and reported. Linked Editorial:  Kottner & Schmitt. Br J Dermatol 2018;179 :549–550 . Plain language summary available online Respond to this article